2018
DOI: 10.2147/ott.s155065
|View full text |Cite
|
Sign up to set email alerts
|

Raptor mediates the antiproliferation of cardamonin by mTORC1 inhibition in SKOV3 cells

Abstract: PurposeCardamonin inhibits the proliferation of SKOV3 cells by suppressing the mammalian target of rapamycin complex 1 (mTORC1). However, the mechanism of cardamonin on mTORC1 inhibition has not been well demonstrated. The regulatory-associated protein of TOR (Raptor) is an essential component of mTORC1. Here, we investigated the role of Raptor in the mTORC1 inhibition effect of cardamonin in SKOV3 cells.MethodsThe expression of Raptor was knockdown by small interfering RNA (siRNA). The expressions of specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 38 publications
0
15
0
Order By: Relevance
“…In this study, we found that carda-monin decreased the phosphorylation of mTOR as well as the expression of NF-κB p65 nuclear protein. In addition, our previous study discovered that cardamonin decreased both the expression and phosphorylation of Raptor, indicating cardamonin may be a specific mTORC1 inhibitor [31]. Therefore, we speculate that the anti-inflammatory effects of cardamonin involve the downregulation of NF-κB activity via the mTOR pathway.…”
Section: Discussionmentioning
confidence: 72%
“…In this study, we found that carda-monin decreased the phosphorylation of mTOR as well as the expression of NF-κB p65 nuclear protein. In addition, our previous study discovered that cardamonin decreased both the expression and phosphorylation of Raptor, indicating cardamonin may be a specific mTORC1 inhibitor [31]. Therefore, we speculate that the anti-inflammatory effects of cardamonin involve the downregulation of NF-κB activity via the mTOR pathway.…”
Section: Discussionmentioning
confidence: 72%
“…cardamonin is a specific mTorc1 inhibitor, which decreases the protein level of raptor, disrupts the interaction of mTor and raptor and interrupts the mTorc1 signalling cascade (24)(25)(26). Therefore, cardamonin inhibits mTor independent of the FrB domain and the kinase domain.…”
Section: Discussionmentioning
confidence: 99%
“…additionally, cardamonin has no effect on the phosphorylation of akt, which is decreased by aZd8055 (24). cardamonin has previously been shown to inhibit the mTorc1 signalling pathway by decreasing the protein level of raptor (24,25). You et al (26) demonstrated that cardamonin exerts cardioprotective effects in left ventricular remodelling by disrupting the mTor-raptor association, suggesting that cardamonin is a specific mTORC1 inhibitor.…”
Section: Anti-proliferative Effect Of Cardamonin On Mtor Inhibitor-resistant Cancer Cellsmentioning
confidence: 99%
“…(2018a) In vitro SKOV3 ↓Glycolysis, HK, LDH, ↑autophagy, LC3-II, ↑LAMP1, ↓p-S6K1, p-mTOR, HK2, ↑p-AMPK Shi et al. (2018b) In vitro SKOV3 ↓Cell viability, ↑autophagy, ↑LC3-II, ↑apoptosis, ↑caspase-3, PARP, ↓Raptor, mTOR, S6K1 Shi et al. (2018c) In vitro SKOV3, A2780 SKOV3 ↓Cell viability, colony formation ↑G2/M phase arrest, ↓XIAP, survivin, Bcl-2, ↓mTOR, p70S6K Niu et al.…”
Section: Biological Activities Of CDmentioning
confidence: 99%